Failure Analysis in Patients With Patellar Redislocation After Primary Isolated Medial Patellofemoral Ligament Reconstruction. Issue 6 (22nd June 2020) - Feucht, Matthias J.; Mehl, Julian; Forkel, Philipp; Achtnich, Andrea; Schmitt, Andreas; Izadpanah, Kaywan; Imhoff, Andreas B.; Berthold, Daniel P.
Background: Reconstruction of the medial patellofemoral ligament (MPFL) has become a popular surgical procedure to address patellofemoral instability. As a consequence of the growing number of MPFL reconstructions performed, a higher rate of failures and revision procedures has been seen. Purpose: To perform a failure analysis in patients with patellar redislocation after primary isolated MPFL reconstruction. Study Design: Case series; Level of evidence, 4. Methods: Patients undergoing revision surgery for reinstability after primary isolated MPFL reconstruction were included. Clinical notes were reviewed to collect demographic data, information on the primary surgery, and the mechanism of patellar redislocation (traumatic vs nontraumatic). Preoperative imaging was analyzed regarding femoral tunnel position and the prevalence of anatomic risk factors (ARFs) associated with patellofemoral instability: trochlear dysplasia (types B through D), patella alta (Caton-Deschamps index >1.2, patellotrochlear index <0.28), lateralization of the tibial tuberosity (tibial tuberosity–trochlear groove distance >20 mm, tibial tuberosity–posterior cruciate ligament [TT-PCL] distance >24 mm), valgus malalignment (mechanical valgus axis >5°), and torsional deformity (internal femoral torsion >25°, external tibial torsion >35°). The prevalence of ARF was compared between patients with traumatic and nontraumatic redislocations and between patients with anatomic and nonanatomic femoral tunnel position. Results: A total of 26 patients (69% female) with a mean age of 25 ± 7 years were included. The cause of redislocation was traumatic in 31% and nontraumatic in 69%. Position of the femoral tunnel was considered nonanatomic in 50% of patients. Trochlear dysplasia was the most common ARF with a prevalence of 50%, followed by elevated TT-PCL distance (36%) and valgus malalignment (35%). The median number of ARFs per patient was 3 (range, 0-6), and 65% of patients had 2 or more ARFs. Patients with nontraumatic redislocations showed significantly more ARFs per patient, and the presence of 2 or more ARFs was significantly more common in this group. No significant difference was observed between patients with anatomic versus nonanatomic femoral tunnel position. Conclusion: Multiple anatomic risk factors and femoral tunnel malposition are commonly observed in patients with reinstability after primary MPFL reconstruction. Before revision surgery, a focused clinical examination and adequate imaging including radiographs, magnetic resonance imaging (MRI), standing full-leg radiographs, and torsional measurement with computed tomography or MRI are recommended to assess all relevant anatomic parameters to understand an individual patient's risk profile. During revision surgery, care must be taken to ensure anatomic placement of the femoral tunnel through use of anatomic and/or radiographic landmarks.